A glimpse into regal heritage: ILM’ LOKA / Farahanie Harun ... [et al.] - Harun, Farahanie; Tuan Mohd Zapri, Tuan Norhanani Nasuha; Mohd Zaliman, Nurin Qistina; Yuserrie, Farid Al-Hakeem (2024)
This idea of a pop-up installation in University Technology MARA, Perak, Malaysia is conceived as a development of a temporary educational venue focused on the architecture of Malay Royal adornments. Designed with sustainability in mind, the space merges the natural elegance of timber with a modern aesthetic welcoming environment for learners. This pop-up is intended to both educate and inspire, providing and distinctive opportunity to delve into the detailed artistry and cultural importance of these traditional artefacts.